2007
DOI: 10.1063/1.2730373
|View full text |Cite
|
Sign up to set email alerts
|

Oblique Hanle Measurements of InAs/GaAs Quantum Dot Spin-Light Emitting Diodes

Abstract: We report on studies of electrical spin injection from ferromagnetic Fe contacts into semiconductor light emitting diodes containing single layers of InAs/ GaAs self-assembled quantum dots ͑QDs͒. An oblique magnetic field is used to manipulate the spin of the injected electrons in the semiconductor. This approach allows us to measure the injected steady-state spin polarization in the QDs, P spin as well as estimate the spin losses in the QD spin detector. After subtraction of magneto-optical effects not relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Such benefits are predicted for fairly modest spin-polarised pumping (S3 pump = 0.25 and 0.38 figure 9) and γ s values consistent with current materials at room temperature. Values of this order may be achievable with spin-aligning electrical contacts [2], [48] for future applications.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Such benefits are predicted for fairly modest spin-polarised pumping (S3 pump = 0.25 and 0.38 figure 9) and γ s values consistent with current materials at room temperature. Values of this order may be achievable with spin-aligning electrical contacts [2], [48] for future applications.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Note the change of sign for equation (A3) compared to equation (6.1-9d) in [48] due to the circular polarisation convention used (here φ = −, +π/2 for RCP,LCP, φ = +, −π/2 for RCP,LCP in [49]). Using the Stokes parameters from (A1) -(A3), ψ can be generated using equation (5).…”
Section: A Stokes Parameters From Complex Linearly Polarized Fieldsmentioning
confidence: 99%
“…It is known that recombination, covered by the fraction of excitons, which are as singlets, is limited to 25%, in case the created excitons ratio of triplet: singlet is 3 : 1 [45]. MNPs doped to emissive layer effect the spin states which resulting in an increase of the singlet exciton fraction and thus recombination process enhances [35,46].…”
Section: Device Performancementioning
confidence: 99%
“…On the other hand, the change in resistance more than 10% was achieved in polyuorene (PFO) devices at room temperature under weak magnetic field of 10 mT [33,34]. The effect of CoPt ferromagnetic nanowires on the exciton formation in poly (2-methoxy, 5-(2-ethylhexiloxy)1, 4-phenylenevinylene) (MEH-PPV) and iridium complex Ir(ppy)3 was investigated by Hu et al [35]. They reported that the spin-polarized holes transferred from CoPt nanowires to the polymer and iridium complex enhance the singlet to triplet ratio in the presence of magnetic field [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation